#### 5.3.1 Cartesian coordinates

5.3.1.1 [328] All boundaries at zero

5.4.0.1 [331] In rectangle
5.4.0.2 [332] On whole plane

##### 5.3.1.1 [328] All boundaries at zero

problem number 328

Solve for $$u(x,y)$$ \begin {align*} \frac {u_{xx}}{A} + \frac {u_{xx}}{B} = -2 \theta \end {align*}

Where $$A,B,\theta$$ are constants, and the boundary conditions are \begin {align*} u(x, -b) &= 0\\ u(x, b) &= 0\\ u(-a, y) &= 0\\ u(a, y) &= 0 \end {align*}

Mathematica

Failed

Maple

sol=()

Hand solution

solve \begin {align*} \frac {u_{xx}}{A}+\frac {u_{yy}}{B} & =-2\theta \\ Bu_{xx}+Au_{yy} & =-2\theta AB\\ & =C \end {align*}

Where $$C=-2\theta AB$$ is a new constant. With boundary conditions\begin {align*} u\left (x,-b\right ) & =0\\ u\left (x,b\right ) & =0\\ u\left (-a,y\right ) & =0\\ u\left (a,y\right ) & =0 \end {align*}

To simplify solution, shift the rectangle so its lower left corner on the origin. Let $$\tilde {x}=x+a$$, and $$\tilde {y}=y+b$$. The boundary conditions becomes\begin {align*} u\left (\tilde {x},0\right ) & =0\\ u\left (\tilde {x},2b\right ) & =0\\ u\left (0,\tilde {y}\right ) & =0\\ u\left (2a,\tilde {y}\right ) & =0 \end {align*}

And the pde becomes $$Bu_{\tilde {x}\tilde {x}}+Au_{\tilde {y}\tilde {y}}=C$$. Instead of keep writing $$\tilde {x},\tilde {y}$$, will use $$x,y$$, but remember that these are shifted version. At the end, we shift back.

Hence the PDE to solve is  $$Bu_{xx}+Au_{yy}=C$$ with BC\begin {align*} u\left (x,0\right ) & =0\\ u\left (x,2b\right ) & =0\\ u\left (0,y\right ) & =0\\ u\left (2a,y\right ) & =0 \end {align*}

Using eigenfunction expansion method. Let \begin {equation} u\left (x,y\right ) =\sum _{n=1}^{\infty }b_{n}\relax (y) X_{n}\left ( x\right ) \tag {1} \end {equation} Where $$X_{n}\relax (x)$$ is eigenfunctions for $$X^{\prime \prime }\left ( x\right ) +\lambda _{n}X\relax (x) =0$$ with boundary conditions $$X\relax (0) =X\left (2a\right ) =0$$. This has eigenfunctions as $$X_{n}\relax (x) =\sin \left (\sqrt {\lambda _{n}}x\right )$$ with eigenvalues $$\lambda _{n}=\left (\frac {n\pi }{2a}\right ) ^{2}$$  for $$n=1,2,\cdots$$.

Substituting (1) into the PDE $$Bu_{xx}+Au_{yy}=C$$ gives$B\sum _{n=1}^{\infty }b_{n}\relax (y) X_{n}^{\prime \prime }\left ( x\right ) +A\sum _{n=1}^{\infty }b_{n}^{\prime \prime }\relax (y) X_{n}\relax (x) =C$ Expanding $$C$$ (a constant) as Fourier sine series the above becomes$B\sum _{n=1}^{\infty }b_{n}\relax (y) X_{n}^{\prime \prime }\left ( x\right ) +A\sum _{n=1}^{\infty }b_{n}^{\prime \prime }\relax (y) X_{n}\relax (x) =\sum _{n=1}^{\infty }q_{n}X_{n}\relax (x)$ But $$X_{n}^{\prime \prime }\relax (x) =-\lambda _{n}X_{n}\relax (x)$$, hence the above becomes\begin {align} -B\sum _{n=1}^{\infty }\lambda _{n}b_{n}\relax (y) X_{n}\relax (x) +A\sum _{n=1}^{\infty }b_{n}^{\prime \prime }\relax (y) X_{n}\left ( x\right ) & =\sum _{n=1}^{\infty }q_{n}X_{n}\relax (x) \nonumber \\ Ab_{n}^{\prime \prime }\relax (y) -B\lambda _{n}b_{n}\relax (y) & =q_{n}\tag {1A} \end {align}

But \begin {align*} C & =\sum _{n=1}^{\infty }q_{n}X_{n}\relax (x) \\ \int _{0}^{2a}CX_{n}\relax (x) dx & =q_{n}\int _{0}^{2a}X_{n}^{2}\left ( x\right ) dx\\ \int _{0}^{2a}C\sin \left (\sqrt {\lambda _{n}}x\right ) dx & =q_{n}\int _{0}^{2a}\sin ^{2}\left (\sqrt {\lambda _{n}}x\right ) dx\\ \frac {-C}{\sqrt {\lambda _{n}}}\left (\left (-1\right ) ^{n}-1\right ) & =q_{n}a\\ q_{n} & =\frac {-C}{a\sqrt {\lambda _{n}}}\left (\left (-1\right ) ^{n}-1\right ) \end {align*}

Hence (1A) becomes$Ab_{n}^{\prime \prime }\relax (y) -B\lambda _{n}b_{n}\relax (y) =\frac {-C}{a\sqrt {\lambda _{n}}}\left (\left (-1\right ) ^{n}-1\right )$ This is standard second order linear ODE. The solution is$b_{n}\relax (y) =D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}y}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}y}+\frac {C}{aB\lambda _{n}^{\frac {3}{2}}}\left (\left (-1\right ) ^{n}-1\right )$ Using the above in (1) gives the solution\begin {equation} u\left (x,y\right ) =\sum _{n=1}^{\infty }\left (D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}y}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}y}+\frac {C}{aB\lambda _{n}^{\frac {3}{2}}}\left (\left (-1\right ) ^{n}-1\right ) \right ) X_{n}\relax (x) \tag {1A} \end {equation} We now need to ﬁnd $$D_{n},E_{n}$$.

Case $$n$$ even

When $$n$$ is even $$\left (\left (-1\right ) ^{n}-1\right ) =0$$ and the solution (1A) becomes$u\left (x,y\right ) =\sum _{n=1}^{\infty }\left (D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}y}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}y}\right ) X_{n}\relax (x)$ At $$y=0$$ the above gives$0=\sum _{n=1}^{\infty }\left (D_{n}+E_{n}\right ) \sin \left (\sqrt {\lambda _{n}}x\right )$ Therefore\begin {equation} D_{n}+E_{n}=0\tag {2} \end {equation} And at $$y=2b$$$0=\sum _{n=1}^{\infty }\left (D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}2b}\right ) \sin \left (\sqrt {\lambda _{n}}x\right )$ Therefore\begin {equation} D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}2b}=0\tag {3} \end {equation} From (2,3) we see that $$D_{n}=E_{n}=0$$, Hence $$u\left (x,y\right ) =0$$ when $$n$$ even.

Case $$n$$ odd

When $$n$$ is odd $$\left (\left (-1\right ) ^{n}-1\right ) =-2$$ and the solution (1A) becomes$u\left (x,y\right ) =\sum _{n=1}^{\infty }\left (D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}y}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}y}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\right ) X_{n}\relax (x)$ At $$y=0$$ the above gives$0=\sum _{n=1}^{\infty }\left (D_{n}+E_{n}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\right ) \sin \left (\sqrt {\lambda _{n}}x\right )$ Therefore\begin {equation} D_{n}+E_{n}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}=0\tag {4} \end {equation} And at $$y=2b$$$0=\sum _{n=1}^{\infty }\left (D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}2b}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\right ) \sin \left (\sqrt {\lambda _{n}}x\right )$ Therefore\begin {equation} D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}2b}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}=0\tag {5} \end {equation} Solving (4,5) for $$D_{n},E_{n}$$ gives\begin {align*} D_{n} & =\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\frac {1}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\\ E_{n} & =\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\frac {e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}} \end {align*}

Therefore the ﬁnal solution from (1A) becomes\begin {align*} u\left (x,y\right ) & =\sum _{n=1,3,5,\cdots }^{\infty }\left (D_{n}e^{\sqrt {\frac {B}{A}\lambda _{n}}y}+E_{n}e^{-\sqrt {\frac {B}{A}\lambda _{n}}y}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\right ) X_{n}\relax (x) \\ & =\sum _{n=1,3,5,\cdots }^{\infty }\left (\left (\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\frac {1}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{\sqrt {\frac {B}{A}\lambda _{n}}y}+\left (\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\frac {e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{-\sqrt {\frac {B}{A}\lambda _{n}}y}-\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\right ) \sin \left (\sqrt {\lambda _{n}}x\right ) \end {align*}

Where $$\lambda _{n}=\left (\frac {n\pi }{2a}\right ) ^{2}$$. Switching back to original coordinates using $$\tilde {x}=x+a$$, and $$\tilde {y}=y+b$$, then the above is$u\left (x,y\right ) =\sum _{n=1,3,5,\cdots }^{\infty }\left (\left (\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\frac {1}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{\sqrt {\frac {B}{A}\lambda _{n}}\left (y+b\right ) }+\left ( \frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\frac {e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e\left (^{-\sqrt {\frac {B}{A}\lambda _{n}}y+b}\right ) -\frac {2C}{aB\lambda _{n}^{\frac {3}{2}}}\right ) \sin \left (\sqrt {\lambda _{n}}\left (x+a\right ) \right )$ Where $$C=-2\theta AB$$, hence\begin {align*} u\left (x,y\right ) & =\sum _{n=1,3,5,\cdots }^{\infty }\left (\left ( \frac {-4\theta AB}{aB\lambda _{n}^{\frac {3}{2}}}\frac {1}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{\sqrt {\frac {B}{A}\lambda _{n}}\left ( y+b\right ) }+\left (\frac {-4\theta AB}{aB\lambda _{n}^{\frac {3}{2}}}\frac {e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{-\sqrt {\frac {B}{A}\lambda _{n}}\left (y+b\right ) }+\frac {4\theta AB}{aB\lambda _{n}^{\frac {3}{2}}}\right ) \sin \left ( \sqrt {\lambda _{n}}\left (x+a\right ) \right ) \\ & =\sum _{n=1,3,5,\cdots }^{\infty }\left (\left (\frac {-4\theta A}{a\lambda _{n}^{\frac {3}{2}}}\frac {1}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{\sqrt {\frac {B}{A}\lambda _{n}}\left (y+b\right ) }+\left ( \frac {-4\theta A}{a\lambda _{n}^{\frac {3}{2}}}\frac {e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}{1+e^{\sqrt {\frac {B}{A}\lambda _{n}}2b}}\right ) e^{-\sqrt {\frac {B}{A}\lambda _{n}}\left (y+b\right ) }+\frac {4\theta A}{a\lambda _{n}^{\frac {3}{2}}}\right ) \sin \left (\sqrt {\lambda _{n}}\left (x+a\right ) \right ) \end {align*}

________________________________________________________________________________________

##### 5.3.1.2 [329] Dirichlet problem in a rectangle

problem number 329

Taken from Mathematica DSolve help pages.

Solve for $$u\left (x,y\right )$$ \begin {align*} u_{xx}+ u_{yy} & = 6x - 6y \end {align*}

Boundary conditions \begin {align*} u(x, 0) &= 1 + 11 x + x^3\\ u(x, 2) &= -7 + 11 x + x^3\\ u(0, y) &= 1 - y^3\\ u(4, y) &= 109 - y^3 \end {align*}

Mathematica

$\left \{\left \{u(x,y)\to x^3+11 x-y^3+1\right \}\right \}$

Maple

$u \left (x , y\right ) = x^{3}-y^{3}+11 x +1$

________________________________________________________________________________________

##### 5.3.1.3 [330] Poisson PDE in whole 2D plane

problem number 330

Solve Poisson PDE $\frac {\partial ^{2}f}{\partial x^{2}}+\frac {\partial ^{2}f}{\partial y^{2}}=6y$

Mathematica

$\left \{\left \{u(x,y)\to c_1(x-i y)+c_2(x+i y)+3 x^2 y\right \}\right \}$

Maple

$u \left (x , y\right ) = 3 x^{2} y +\textit {\_F1} \left (-i x +y \right )+\textit {\_F2} \left (i x +y \right )$

Hand solution

Solve Poisson PDE $\frac {\partial ^{2}f}{\partial x^{2}}+\frac {\partial ^{2}f}{\partial y^{2}}=6y$

The solution is \begin {equation} f=f_{h}+f_{p}\tag {1} \end {equation} Where $$f_{h}$$ is the homogenous solution to Laplace $$\frac {\partial ^{2}f}{\partial x^{2}}+\frac {\partial ^{2}f}{\partial y^{2}}=0$$ and $$f_{p}$$ is a particular solution. The homogeneous solution is easily found as follows. Let $f_{h}=F\left (mx+y\right )$ Then $$\frac {\partial f_{h}}{\partial x}=mF^{\prime }$$ and $$\frac {\partial ^{2}f_{h}}{\partial x^{2}}=m^{2}F^{\prime \prime }$$ and $$\frac {\partial f_{h}}{\partial y}=F^{\prime }$$ and $$\frac {\partial ^{2}f_{h}}{\partial y^{2}}=F^{\prime \prime }$$. Substituting these into $$\frac {\partial ^{2}f_{h}}{\partial x^{2}}+\frac {\partial ^{2}f_{h}}{\partial y^{2}}=0$$ gives\begin {align*} m^{2}F^{\prime \prime }+F^{\prime \prime } & =0\\ m^{2}+1 & =0\\ m & =\pm i \end {align*}

Since we assumed $$f_{h}=F\left (mx+y\right )$$, then the homogeneous solution is sum of two arbitrary functions (one for each root of $$m$$)$f_{h}=F_{1}\left (ix+y\right ) +F_{2}\left (-ix+y\right )$ To ﬁnd particular solution, let \begin {equation} f_{p}=Ax^{n}y^{m}\tag {2} \end {equation} Hence $$\frac {\partial f_{p}}{\partial x}=Anx^{n-1}y^{m}$$ and $$\frac {\partial ^{2}f_{p}}{\partial x^{2}}=An\left (n-1\right ) x^{n-2}y^{m}$$ and $$\frac {\partial f_{p}}{\partial y}=Ax^{n}my^{m-1}$$ and $$\frac {\partial ^{2}f_{p}}{\partial y^{2}}=Ax^{n}m\left (m-1\right ) y^{m-2}$$. Substituting these into $$\frac {\partial ^{2}f_{p}}{\partial x^{2}}+\frac {\partial ^{2}f_{p}}{\partial y^{2}}=6y$$ gives\begin {align*} An\left (n-1\right ) x^{n-2}y^{m}+Ax^{n}m\left (m-1\right ) y^{m-2} & =6y\\ y^{m}\left (An\left (n-1\right ) x^{n-2}+Ax^{n}m\left (m-1\right ) y^{-2}\right ) & =6y \end {align*}

Comparing terms, then $$m=1$$ and $An\left (n-1\right ) x^{n-2}+Ax^{n}m\left (m-1\right ) y^{-2}=6$ Since $$m=1$$ then the above simpliﬁes to$An\left (n-1\right ) x^{n-2}=6$ Since there is no $$x$$ in RHS, then $$n-2=0$$ or $$n=2$$ and the above becomes\begin {align*} 2A\left (2-1\right ) & =6\\ A & =3 \end {align*}

Hence (2) becomes$f_{p}=Ax^{n}y^{m}=3x^{2}y$ And the complete solution (1) is\begin {align*} f\left (x,y\right ) & =f_{h}+f_{p}\\ & =F_{1}\left (ix+y\right ) +F_{2}\left (-ix+y\right ) +3x^{2}y \end {align*}